(untitled) (Journal of Social Sciences Review, 2023)
This study was intended to investigate the ‘Relationship between Autocratic Leadership Style and Teachers’ Job Performance’. The main objective of the study was, ‘To find out the relationship between autocratic leadership style and teachers’ job performance’. All secondary school teachers (SSTs) of the three chosen districts of Khyber Pakhtunkhwa, i.e. Kohat, Peshawar and Buner were included in the target population of this research. Sample of this survey was selected from secondary schools of the three mentioned districts. The total number of secondary school teachers of the selected districts was 1092. Two closed ended research tools, Leadership Styles Questionnaire and Teachers’ Job Performance Questionnaire were developed. Reliability of total item correlation of the two questionnaires were found out using Cronbach’s Alpha which were 0.817 for Leadership Styles Questionnaire (LSQ) while 0.916 for Teachers’ Job Performance Questionnaire (TJPQ). On the basis of data analysis, the null hypothesis was rejected. Based on the findings of the study, secondary school heads (Headmasters and Principals) are recommended to help the teachers in classroom management, for improving their teaching skills, management skills, discipline, regularity and interpersonal skills. It is also recommended that special workshops, seminars and trainings on capacity building of the teachers may be arranged for enhancing their capabilities and overall improvement of the institutions.